NSUN2 promotes colorectal cancer progression and increases lapatinib sensitivity by enhancing CUL4B/ErbB‐STAT3 signalling in a non‐m5C manner - Yuanbo Hu; Chenbin Chen; Kezhi Lin; Xinya Tong; Tingting Huang; Tianle Qiu; Xietao Chen; Jun Xu; Wangkai Xie; Xiangwei Sun; Shiyu Feng; Mingdong Lu; et al. (Clinical and Translational Medicine)
Abstract NSUN2, a major methyltransferase that catalyzes m5C methylation in eukaryotes, is known to be implicated in the development of multiple cancers. However, its role in colorectal cancer (CRC) and the related molecular mechanisms have yet to be sufficiently determined. Here, we conducted an analysis of public database (722 CRC patients) and two distinct cohorts from our centre (1559 CRC patients), which revealed that NSUN2 is upregulated in CRC and correlates with unfavourable prognosis. Our analyses also showed that NSUN2 promotes the proliferation and metastasis capabilities of CRC cells. Intriguingly, NSUN2 was found to promote CRC via an m5C‐independent mechanism, which has not been previously reported. Overexpression of both wild‐type and m5C enzymatic‐dead mutant NSUN2 upregulated and activated the ErbB‐STAT3 signalling pathway. We also found that both wild‐type and the m5C enzymatic‐dead mutant NSUN2 closely interacted with CUL4B. Silencing of CUL4B effectively inhibited the m5C‐independent function of NSUN2. Moreover, overexpression of NSUN2 enhanced the sensitivity of CRC cells to lapatinib. Taken together, our findings revealed a novel m5C‐independent mechanism for NSUN2 in the malignancy and lapatinib sensitivity of CRC via activation of the CUL4B/ErbB‐STAT3 pathway, which provides a potential therapeutic strategy for patients with CRC. Highlights NSUN2 is upregulated in CRC and associated with poor prognosis of CRC patients. NSUN2 promotes CRC malignancy independently of its m5C‐enzymatic activity, a mechanism that has not been previously reported. The non‐m5C carcinogenic roles of NSUN2 may be mediated through interactions with CUL4B, thereby activating the ErbB‐STAT3 signalling pathway. NSUN2‐mediated upregulation of ErbB‐STAT3 pathway enhances the sensitivity of CRC to lapatinib treatment.